2017
DOI: 10.1056/nejmcp1605501
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in Hospitalized Older Adults

Abstract: A 75-year-old man is admitted for scheduled major abdominal surgery. He is functionally independent, with mild forgetfulness. His intraoperative course is uneventful, but on postoperative day 2, severe confusion and agitation develop. What is going on? How would you manage this patient’s care? Could his condition have been prevented?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
635
2
63

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 740 publications
(772 citation statements)
references
References 50 publications
14
635
2
63
Order By: Relevance
“…Older age, dementia, alcohol misuse, major surgery, comorbidities and severity of illness have been reported as strong risk factors for delirium . We also found that ward patients with delirium were older, more likely to have dementia and close to 10 times more likely to be receiving chronic psychotropic drugs supporting the need for a multicomponent approach to delirium …”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Older age, dementia, alcohol misuse, major surgery, comorbidities and severity of illness have been reported as strong risk factors for delirium . We also found that ward patients with delirium were older, more likely to have dementia and close to 10 times more likely to be receiving chronic psychotropic drugs supporting the need for a multicomponent approach to delirium …”
Section: Discussionsupporting
confidence: 68%
“…Knowledge on delirium in hospitalised patients is limited to specific populations (geriatric wards, palliative care units, ICU and major surgery wards) all reporting a high incidence . However, various diagnostic tools were used which are not sufficiently versatile to be applied to every setting, making comparisons difficult and large‐scale investigations of delirium difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POD is an acute brain dysfunction associated with increased morbidity and healthcare costs (Marcantonio, 2017, Palanca et al , 2017). It is unclear whether intraoperative burst-suppression causes POD or merely reflects susceptibility to POD.…”
Section: Introductionmentioning
confidence: 99%
“…A history of POD has been strongly associated with a long-term cognitive decline (Saczynski et al , 2012, Inouye et al , 2016, Marcantonio, 2017). Further, patients with cognitive impairment on cognitive screening tests are more likely to be diagnosed with POD (Kalisvaart et al , 2006, Robinson et al , 2012, Saczynski et al , 2012, Inouye et al , 2016, Culley et al , 2017).…”
Section: Introductionmentioning
confidence: 99%